Trisyllabic shortening in English: past and present - Lahiri, A; Fikkert, P (Cambridge University Press, 1999)
Trisyllabic shortening or TSS is one of the most controversial processes in the history of English. Time after time, claims have been made about quantity variations, attributing them either to trisyllabic shortening, closed syllable shortening, or other mechanisms. Our examination of the nature of TSS in the history of English leads us to conclude that it differs from closed syllable shortening, which is syllable based, and that the preference for a maximal foot has remained the underlying incentive for maintaining vowel quantity variations throughout the centuries. However, the prosodic system has undergone dramatic changes and many features of TSS in the older and modern stages are not the same. Older TSS affected mostly inflected native words, while in Modern English, TSS causes alternations in derivationally related words with Romance suffixes. Interacting with open syllable lengthening, older TSS led to quantity alternations in inflectional paradigms which were later levelled out. Romance loans, both suffixed and nonsuffixed forms, were borrowed in their entirety and constrained by the prosodic structure of the language. Only later, when these words came to be derivationally related, were quantity alternations observable with TSS operating as a constraint dictated by the prosodic structure of the modern language. Thus, throughout the history of English, TSS has served the same purpose: it led to the preferred prosodic structure of the word.